GUIDANCE OF LEARNING VISITS ON THE IMPLEMENTATION OF LOVE, PRIDE AND UNDERSTANDING OF THE RUPIAH AT BANK INDONESIA - Y. Flora Hosio; Rachel Pelly; Detrina Kafiar; Chelvin Rumbiak; Jeremy Hamadi; Nikson Meop; Maikel Yalehatu (RADJA PUBLIKA, 2025)
Study visit activities as community service activities that aim to provide understanding to students and accompanying lecturers from Bank Indonesia office employees in Papua as resource persons in the study visit. The methods or stages in implementing this service are the preparation stage, the implementation stage and the evaluation stage. The results of the service activities in the form of study visits have been carried out, so it can be concluded that the process of understanding the initial stage of Love for Rupiah, Proud and Understand Rupiah. With several criteria for love, pride and understanding of the rupiah, we are taught next, besides this activity has been realized for this activity for a study visit by the Community Service team from students and accompanying lecturers at the Faculty of Economics & Business, Ottow Geissler University Papua has proven that understanding of Love, Pride and Understand Rupiah as money with the best design in 2023 in Mexico today as love for Indonesia in the Land of Papua